Highly In‐Plane Anisotropic 2D GeAs2 for Polarization‐Sensitive Photodetection. Issue 50 (14th October 2018) - Li, Liang; Gong, Penglai; Sheng, Daopeng; Wang, Shuao; Wang, Weike; Zhu, Xiangde; Shi, Xingqiang; Wang, Fakun; Han, Wei; Yang, Sanjun; Liu, Kailang; Li, Huiqiao; et al.
Abstract: Due to the intriguing anisotropic optical and electrical properties, low‐symmetry 2D materials are attracting a lot of interest both for fundamental studies and fabricating novel electronic and optoelectronic devices. Identifying new promising low‐symmetry 2D materials will be rewarding toward the evolution of nanoelectronics and nano‐optoelectronics. In this work, germanium diarsenide (GeAs2 ), a group IV–V semiconductor with novel low‐symmetry puckered structure, is introduced as a favorable highly anisotropic 2D material into the rapidly growing 2D family. The structural, vibrational, electrical, and optical in‐plane anisotropy of GeAs2 is systematically investigated both theoretically and experimentally, combined with thickness‐dependent studies. Polarization‐sensitive photodetectors based on few‐layer GeAs2 exhibit highly anisotropic photodetection behavior with lineally dichroic ratio up to ≈2. This work on GeAs2 will excite interests in the less exploited regime of group IV–V compounds. Abstract : A new 2D material, GeAs2, with high anisotropy is introduced. A strong interlayer interaction is revealed through large, thickness‐dependent Raman frequency shifts. The structural, vibrational, electrical, and optical in‐plane anisotropy of GeAs2 is investigated theoretically and experimentally. Moreover, a remarkable anisotropic photoresponsivity with linearly dichroic ratio up to ≈2 is realized in a polarization‐sensitive photodetector based on few‐layer GeAs2 .